PERANCANGAN LOGO DAN MEDIA PROMOSI PARIWISATA ISLAMI DI PULAU PENYENGAT MENGGUNAKAN TEKNIK FOTOGRAFI LANDSCAPE SEBAGAI UPAYA MENINGKATKAN BRAND AWARENESS - Yudhi Martha Nugraha; Nor Azlin Binti Hamidon (Lembaga Penelitian Universitas Trisakti, 2018)
The purpose of designing the logo and promotional media penyengat island is to make a islamic tourist attraction in kepri (riau archipelago). The research was conducted with qualitative methods of doing interviews, documentation, observation and literature study to get the data used to support the manufacture of logo design concepts and media promotion. The concept in this study was obtained from the SWOT analysis, STP, and USP then the adjective derived dikerucutkan back so